192 An Audit of The Delivery of Paediatric Orthopaedic Services at The Bristol Royal Children's Hospital in Response to The British Orthopaedic Association Standards for Trauma (BOAST) COVID-19 Guidance. (4th May 2021) - Benning, M S; Berwin, J; Monsell, F; Carpenter, C; Kendall, J; Crosswell, S; Thomas, S; Knapper, T
Abstract: Introduction: Guidance from the BOAST helped structure our paediatric orthopaedic service n response to COVID-19. We assessed our compliance with 'BOAST COVID-19 standards', whether it is possible to run a safe and effective paediatric orthopaedic service. Method: We performed a prospective audit of clinic and theatre data (16th March to 30th April 2020), from the paediatric orthopaedic department at the BRCH against the 'BOAST COVID-19 standards'. We also performed a retrospective audit. Results: Patients booked into acute fracture clinic (AFC) and fracture clinic follow-up (FFO) reduced by 40% and 48% respectively from 2019 to 2020. A virtual fracture clinic (VFC) was implemented with an increasing trend seen. The number of patient initiated follow-up appointments increased in AFC and FFO from 16% to 75% and 12% to 35% respectively. Radiography was reduced; only 17% and 39% of AFC and FFO patients respectively required radiographs. On-call referrals and trauma cases dropped by 50% with similar case mix year-on-year. All elective operating was cancelled in 2020. Conclusions: By reducing clinic admissions and theatre throughput, it was possible to run an effective paediatric orthopaedic service in a busy tertiary referral centre. Our aim now is to determine the long-term efficacy, cost, and sustainability of our COVID-19 service.